How to design and deliver a local teaching program. Issue 6 (July 2017) - Limb, Christopher; Whitehurst, Katharine; Gundogan, Buket; Koshy, Kiron; Agha, Riaz
Abstract : Teaching is an invaluable aspect of any medical or surgical career. Many trainees will find themselves delivering teaching at several stages in their career and in this "How to" article we explain how to design, set up, and deliver a successful teaching program, as well as how to evidence this in your portfolio.